Art-house film and its dissemination on the Czech market - Blažková, Eva (Iluminace, 2016)
Information about the author's forthcoming dissertation, which aims to analyse the economic mechanisms that influence the introduction of art film into Czech cinemas.
Keywords: art film; economics and film; independent film